Safe and efficient method for cryopreservation of human induced pluripotent stem cell-derived neural stem and progenitor cells by a programmed freezer with a magnetic field. (June 2016) - Nishiyama, Yuichiro; Iwanami, Akio; Kohyama, Jun; Itakura, Go; Kawabata, Soya; Sugai, Keiko; Nishimura, Soraya; Kashiwagi, Rei; Yasutake, Kaori; Isoda, Miho; Matsumoto, Morio; Nakamura, Masaya; et al.
Highlights: CAS cryopreservation improved cell survival immediately after thawing. CAS did not significantly affect proliferation, differentiation or gene expression. We found the optimal and useful freezing method of hiPSC-NS/PCs. This method enables us to apply allogeneic transplantation for SCI patients. Abstract: Stem cells represent a potential cellular resource in the development of regenerative medicine approaches to the treatment of pathologies in which specific cells are degenerated or damaged by genetic abnormality, disease, or injury. Securing sufficient supplies of cells suited to the demands of cell transplantation, however, remains challenging, and the establishment of safe and efficient cell banking procedures is an important goal. Cryopreservation allows the storage of stem cells for prolonged time periods while maintaining them in adequate condition for use in clinical settings. Conventional cryopreservation systems include slow-freezing and vitrification both have advantages and disadvantages in terms of cell viability and/or scalability. In the present study, we developed an advanced slow-freezing technique using a programmed freezer with a magnetic field called Cells Alive System (CAS) and examined its effectiveness on human induced pluripotent stem cell-derived neural stem/progenitor cells (hiPSC-NS/PCs). This system significantly increased cell viability after thawing and had less impact on cellular proliferation and differentiation. We further found that frozen-thawed hiPSC-NS/PCs were comparable with non-frozen ones at the transcriptome level. Given these findings, we suggest that the CAS is useful for hiPSC-NS/PCs banking for clinical uses involving neural disorders and may open new avenues for future regenerative medicine.